Do Unions Cause Job Dissatisfaction? Evidence from a Quasi‐Experiment in the United Kingdom. (18th May 2020) - Bessa, Ioulia; Charlwood, Andy; Valizade, Danat
Abstract: Unionized workers tend to be less satisfied with their jobs than their non‐union counterparts. Despite 40 years of research that has sought to explain this phenomenon, the causes of this relationship are not fully understood. Drawing on nationally representative panel data from the UK, this study uses quasi‐experimental methods to compare how the job satisfaction of union members and their non‐union counterparts changes in response to an exogenous event. Results suggest that working conditions rather than the behaviour of unions are the more likely cause of union member job dissatisfaction.